PENGUKURAN KINERJA PELAYANAN PADA KANTOR BERSAMA SAMSAT MANYAR SURABAYA - Prastama, Angger Yudy (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this to find out how the performance of Kantor Bersama Samsat Manyar Surabaya Timur which is located on jalan Manyar Kertoarjo No. 1 Surabaya which is measured by using Community Satisfaction Index and to find out how the suitability level between service performance an public expectation. The data analysis technique is using qualitative descriptive design in order to find out community satisfaction index which is calculate by using weighted average value from each service element based on the number of KEP/25/M.PAN/2/2004. The result of research at Kantor Bersama Samsat Manyar Surabaya Timur shows that performance measurement which is appraised from the Community Satisfactiton Index is obtained from each indicator (service procedures, service requirement, service officers clarity, service officers disciplinary, service officers responsibility, service officers ability, service rapidity, service equality, officers hospitality and politeness, reasonable service cost, certainty of service cost, certainty of service schedule, service convenience, service security) is in good position and result of index is 3.00543 Ã 25 = 75.14 which means the service unit performance is good while the suitability level between public expectation and performance is 90.54% the service performance is in appropriate whit the public expectation. Keywords: community satisfaction index, performance measurement, publik service.